2010
DOI: 10.1007/s00384-010-0887-8
|View full text |Cite
|
Sign up to set email alerts
|

Damage control with abdominal vacuum therapy (VAC) to manage perforated diverticulitis with advanced generalized peritonitis—a proof of concept

Abstract: Damage control with lavage, limited bowel resection, VAC, and scheduled second-look operation represents a feasible strategy in patients with perforated diverticulitis (Hinchey III and IV) to enhance sepsis control and improve rate of anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 28 publications
1
66
0
2
Order By: Relevance
“…In a non-randomized study of 27 consecutive patients with perforated diverticulitis (Hinchey III/IV), the patients were managed either with sigmoid resection and primary anastomosis, or limited sigmoid resection or suture, open abdomen and primary anastomosis or colostomy at second operation 24–48 hours later, or Hartmann procedure; sigmoid resection and end colostomy [117]. All 6 patients with primary anastomosis survived without complications, but there was an obvious selection bias.…”
Section: Source Controlmentioning
confidence: 99%
“…In a non-randomized study of 27 consecutive patients with perforated diverticulitis (Hinchey III/IV), the patients were managed either with sigmoid resection and primary anastomosis, or limited sigmoid resection or suture, open abdomen and primary anastomosis or colostomy at second operation 24–48 hours later, or Hartmann procedure; sigmoid resection and end colostomy [117]. All 6 patients with primary anastomosis survived without complications, but there was an obvious selection bias.…”
Section: Source Controlmentioning
confidence: 99%
“…Improvements in TAC techniques, however, led to higher fascial closure rates [54]. Recent studies have indeed shown DCS to be a feasible technique in patients with generalized peritonitis [55,56]. …”
Section: Damage Control Surgerymentioning
confidence: 99%
“…These were the techniques used in our AVS management, which allowed for effective peritoneal drainage and also protected the open wound from contamination with enteric contents. In addition, the gauze dressings should be changed frequently, every 2–3 days, even without macroscopic pollution [14]. …”
Section: Discussionmentioning
confidence: 99%